Development of lamivudine containing multiple emulsions stabilized by gum odina - Aditya Kumar Jena; Amit Kumar Nayak; Arnab De; Debmalya Mitra; Amalesh Samanta (Future Journal of Pharmaceutical Sciences, 2018)
In the current study, a multiple emulsion (W/O/W) of lamivudine was developed using a new biopolymer, gum odina (GOd) to increase bioavailability and patient compliances. GOd was employed to stabilize both the interfaces of liquid membrane in both the external and internal aqueous phases. The developed W/O/W multiple emulsion of lamivudine was characterized by analyzing droplet size, zeta potential, polydispersity index (PDI), sedimentation, viscosity, rheological properties, drug entrapment efficiency, in-vitro drug release and stability at various storage conditions. The results obtained were also compared with W/O/W multiple emulsion of lamivudine prepared using Tween 80 (a standard emulsion stabilizer). The drug entrapment efficiency of W/O/W multiple emulsion stabilized using GOd was measured as 91.60 ± 3.66% with sustained lamivudine release over a period of 6 h. Rheological and microscopic examinations indicated long term stability of the developed emulsion prepared using GOd. The results of the current study provide a promising scope to attain sustained drug release through the W/O/W multiple emulsions stabilized by GOd in antiviral therapies. Keywords: Gum odina, Lamivudine, Multiple emulsions